2019
DOI: 10.3390/ijms20153762
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete Spinal Cord Injury Reverses the Level-Dependence of Spinal Cord Injury Immune Deficiency Syndrome

Abstract: Spinal cord injury (SCI) is associated with an increased susceptibility to infections, such as pneumonia, which is the leading cause of death in these patients. This phenomenon is referred to as SCI immune deficiency syndrome (SCI-IDS), and has been shown to be more prevalent after high-level transection in preclinical SCI models. Despite the high prevalence of contusion SCIs, the effects of this etiology have not been studied in the context of SCI-IDS. Compared to transection SCIs, which involve a complete lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…Additionally, we found that in parallel to increased cell number in lumbar lymph node, the number of apoptotic cells also increased in lumbar lymph node on 7 days after injury. In agreement with our data, it has been recently demonstrated that thoracic spinal cord injury could enhance significantly apoptosis in spleen 3 and 7 days after thoracic spinal cord injury in rats [23,24]. Therefore, results obtained from the present study revealed a possible mechanism by which anatomical position and lymphatic pathways of CNS regional draining lymph nodes to the spinal cord could originate the differential immune response to spinal cord injury.…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, we found that in parallel to increased cell number in lumbar lymph node, the number of apoptotic cells also increased in lumbar lymph node on 7 days after injury. In agreement with our data, it has been recently demonstrated that thoracic spinal cord injury could enhance significantly apoptosis in spleen 3 and 7 days after thoracic spinal cord injury in rats [23,24]. Therefore, results obtained from the present study revealed a possible mechanism by which anatomical position and lymphatic pathways of CNS regional draining lymph nodes to the spinal cord could originate the differential immune response to spinal cord injury.…”
Section: Discussionsupporting
confidence: 93%
“…2a). Previous studies have reported altered levels of NE in the spleen in response to SCI [2,5,13] weeks after the injury was performed. Here we show that increased levels of NE in the spleen can be detected as early as 1 dpi (t = 4.171; df = 6.134; p = 0.006) ( Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Several systemic immune alterations have been documented after SCI. Studies demonstrate that SCI can promote proinflammatory responses damaging peripheral organs [28,29], to others showing deficient immune responses to pathogens or severe immunosuppression [1,[3][4][5]13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, experiments in a rat model clearly demonstrated similar differences in the secretion of the vascular endothelial growth factor (VEGF), leptin, interferon-γ-induced chemokine IP- 10, IL-10, IL-18, the granulocyte colony-stimulating factor (G-CSF), and chemokine fractalkine in animals’ plasma. In contrast to the thoracic spine trauma, injury to the cervical spine is accompanied by a reduced expression of these mediators; this is probably due to sympathetic dysregulation, which is associated with higher injury severity [ 67 , 68 ]. Experiments on mice have also demonstrated that the involvement of the cytokine profile in the systemic changes of interleukins such as IL-3, IL-6, IL-10, IL-13, and G-CSF after a spinal cord injury to the lower thoracic region (Th910) is accompanied by the activation of T lymphocytes and neutrophils during the immediate post-traumatic phase of the observed changes [ 69 ].…”
Section: Immune and Cytokine Responses During The Acute Post-traummentioning
confidence: 99%